Quantum gravity and its preponed birth - Saxena, Ashok; Saxena, Ashwarya; Saxena, Amit (India Notion Press, 2023)
The Geometrical string theory TREO MODEL is a compelling theory that challenges our understanding of the universe. By introducing energy as the fifth dimension, the model transforms the traditional space-time continuum into an omnipresent space matrix with three interdependent components: Space, Time, and Energy. According to the model, the contraction of space causes kinetic energy to erupt, and time to slow down. As the matrix contracts layer by layer in increasing number of dimensions of Space-time, it forms the fields of all four basic forces, including gravity. While the figure on the front cover page, suggests that all bodies are pushed equally from all sides to be supported, the model proposes that when another body comes into the gravitational field of any body, both bodies get inadequate support from the common shared space matrix in between. This leads to the falling of bodies towards each other, which is perceived as the gravitational attraction of the other body.
Keywords: Quantum gravity